PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP PROFITABILITAS dengan INFORMASI AKUNTANSI SEBAGAI VARIABEL MODERASI (Studi Empiris Perusahaan Go Publik di BEI) - Andoyo, Sony Wisnu (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2019)
The purpose of this research is to know the influence of corporate social responbility of the profitability of the company with its accounting information as a moderating variable. This research was conducted on the Indonesia stock exchange in the fiscal year 2011 and 2012. Determination of the sample using a purposive sampling method so that derived 68 observations. Statistical analysis including classical assumptions and test  the feasibility of the model. Testing the influence of variable pemoderasi in this research hypothesis was tested with a moderated regression analysis (MRA) which is a special application of linear multiple regression. Based on the research results and discussion it can be concluded that although the corporate social responbility proven does not affect the company's profitability with the power of accounting information as a moderating variable but many benefits derived pelaksanan company with corporate social responsibility, among others, products are increasingly preferred by consumers and companies are of interest to investors. Corporate social responsibility can be used as a tool of marketing recently for the company when it implemented sustainable. However, by implementing CSR, corporate image will be the better so that consumer loyalty higher. Along with the increasing consumer loyalty in a long time, then the sale of the company will be more improved, and in the end with the implementation of CSR, expected level of profitability the company also increased